Cu–Cu joint with great strength using In/Sn–58Bi hybrid soldering at low temperature (90 °C) - Yu-An Shen (Journal of Materials Research and Technology)
This study investigates Cu single-sided solder joints using hybrid soldering (In + Sn58Bi) at reflow temperatures ranging from 80 to 130 °C. The wetting angles of 27° at 90 °C and 22° at 130 °C demonstrated good wettability. The hybrid solders were composed of γ-In(Sn, Bi) and Bi(In, Sn)2 phases, forming Cu6(In, Sn)5 interfacial intermetallic compounds (IMCs). Thermodynamic calculations proved that the hybrid soldering possessed a low liquid temperature of 86.8 ° C, making it suitable for low-temperature applications. The hybrid solders demonstrated notable mechanical performance, with microhardness values exceeding 10 HV—higher than Sn–52In solder (6 HV). Sandwich hybrid-solder joints, reflowed at 90 and 130 ° C, outperformed Sn–52In soldering strength (30.1 and 35.5 MPa) by over 135% and 175%. Additionally, the hybrid solder contains only 41.9 wt% In, lower than Sn–52In, reducing material costs. This study reveals the hybrid solder system offers a promising low-cost and good-strength solution for low-temperature soldering applications.